Penyuluhan Tentang Dampak Positif Penggunaan Gadget Bagi Anak Usia Dini - Rusnedy, Hidayati; Tanjung, Lailatul Syifa; Hidayat, Hidayat; Priyatno, Arif Mudi (Institute Of Advanced Knowledge and Science, 2024)
The Golden Age period is for children aged 0-6 years, where during this period children's development develops rapidly and must develop well, this is because during this period children have potential in something and have a very great curiosity. It is seen that children often wonder about what they see. The use of gadgets, especially smartphones and tablets in early childhood, has now become a public concern. The reason is, gadgets have become a necessity for society and even children. Gadgets are technology that have very interesting applications and features, such as games and videos that children really like. Most parents do not pay attention to and regulate their children's use of gadgets and sometimes parents do not realize that their children are addicted to gadgets. This outreach aims to provide knowledge to parents and teachers that if the use of gadgets is carried out with supervision and used properly it will have a positive impact which is very useful for children's development, be it physical, emotional and intelligence development